Gambaran Kemiskinan Dalam Novel Kawi Matin Di Negeri Anjing Dan Dunia Kecil Yang Riuh Karya Arafat Nur - Rahma Binta Monica; Asrofah Asrofah; Murywantobroto Murywantobroto (STIKes Ibnu Sina Ajibarang, 2024)
This research is motivated by one of the conflicting problems in the form of appreciation of life in society, namely poverty. This poverty is associated with the literary works of Kawi Matin di Negeri Anjing and Dunia Kecil yang Riuh Novel by Arafat Nur. The method applied in this research is a literary sociology approach along with the five dimensions of poverty. This research aims to determine the depiction of poverty in the novel Kawi Matin di Negeri Anjing and Dunia Kecil yang Riuh using sociological literature studies. Method Data collection was carried out using literature study techniques. This research uses qualitative research. The steps used in processing this research data were looking for references such as books, journals, etc., reading the entire contents of the two novels, understanding and marking statements that describe poverty, classifying the data based on problems, and carrying out analysis. The results of this research show that there were 116 data points related to five dimensions of poverty and their impacts: basic poverty, helplessness, vulnerability to emergency situations, dependency, and alienation, as contained in the novels Kawi Matin di Negeri Anjing and Dunia Kecil yang Riuh. The suggestions that the author can convey in this research can be used as reference material in conducting research on different topics or by increasing the novelty of future research.